2013
DOI: 10.1111/bjh.12587
|View full text |Cite
|
Sign up to set email alerts
|

The role of TLR4 in pathophysiology of antiphospholipid syndrome‐associated thrombosis and pregnancy morbidity

Abstract: SummaryThe antiphospholipid syndrome (APS) is an autoimmune disease characterized by the clinical features of recurrent thrombosis in the venous or arterial circulation and fetal losses. Antiphospholipid antibodies (aPL), particularly against the phospholipid binding protein beta-2 glycoprotein I (b2GPI), play an important role in APS pathological mechanisms. aPL can activate intracellular signal transduction in a b2GPI-dependent manner to induce inflammatory responses, and promote hypercoagulable state and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 108 publications
0
29
0
2
Order By: Relevance
“…Recent studies have suggested a role for TLR4 signaling in promoting thrombosis, [21][22][23][24] and the EDA segment of cFn, but not other domains, is known to activate human TLR4 expressed in HEK293 cells via myeloid differentiation-2. 16 Interestingly, polymorphisms in human TLR4 have been associated with increased atherothrombotic risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested a role for TLR4 signaling in promoting thrombosis, [21][22][23][24] and the EDA segment of cFn, but not other domains, is known to activate human TLR4 expressed in HEK293 cells via myeloid differentiation-2. 16 Interestingly, polymorphisms in human TLR4 have been associated with increased atherothrombotic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated that cellular Fn-EDA1 interacts with the innate immune receptor TLR4, which has been shown to play a role in modulating thrombosis in the presence of its exogenous and endogenous ligands. [21][22][23][24]30 To determine whether TLR4 contributes to cellular Fn-EDA1-mediated accelerated arterial thrombosis, we generated Fn-EDA 1/1 mice on a TLR4-deficient background (Fn-EDA…”
Section: Tlr4 Contributes To Cellular Fn-eda1-mediated Accelerated Thmentioning
confidence: 99%
See 1 more Smart Citation
“…and 174 the right carotid artery was exposed. A 1 × 1.5 mm strip of in vitro assays, TLR4 plays important roles in aPL-induced TF 308 activity/expression [24,25]. Therefore, we first measured 309 the TF activity in peritoneal macrophages and carotids 310 harvested from experimental animals injected with NR-IgG, 311 anti-β2GPI, or IgG-APS.…”
mentioning
confidence: 99%
“…The birth of a new life is an extremely complex and regulated process, and involves the immunological interactions between maternal and paternal gametes, the maternal immunological function, expression of genes inherited from both parents, and chromosome structure (Wilding et al, 2004;Burrough et al, 2011;Turner et al, 2012;Xie et al, 2014). At present, habitual abortion not only seriously affects the patient's psychological and physiological health, but the quality of life of the patient's family.…”
Section: Discussionmentioning
confidence: 99%